Makna Harap-Harap Cemas dalam Qasidah Burdah: Kajian Analisis Semiotika (LPTNU Sumenep, 2023)
The purpose of this article is to discuss the meanings contained in the Burdah Qasidah, specifically the poem of Al-Bushiri in verses 140-160, based on semiotic analysis. The method used to uncover the meaning of the poem is descriptive qualitative research, which will describe the hopes and anxieties conveyed in the Qasidah Burdah by Al-Bushiri. The object of this research is the verses found in lines 140-160, focusing on the concepts of fear (khouf) and hope (roja'), as well as regrets/worries. The research highlights Al-Bushiri's concept of hope and anxiety based on factual evidence. The results of the research indicate that the term